Comparative study of hydatid cysts isolated from livers of different hosts (Baghdad Science Journal, 2025)
Fifty three hydatid cysts were collected from different hosts, sheep, goats and cattle , from many slaughterhouse in Salahadin and Baghdad , while human's hydatid cysts samples were collected from Tikrit educational hospital and Tofiqe civilian hospital patients . The study included a biochemical comparison of some hydatid cyst fluid criteria such as, glucose, total protein, pH, glutamate pyrovate transaminase enzyme (GPT) , glutamate oxaloacetate transaminase enzyme (GOT) , acid phosphatase (ACP) , Alkaline Phosphatase (ALP) , and also studied protoscolices viability,the current study showed the differences in chemical composition of hydatid cyst fluids back to host type and parasite strain .